Study of causes and risk factors of perinatal mortality in Al Ameen Medical College, Vijayapur - Abhishek Ray; V.A. Thobbi; V.R. Dandavate (Al Ameen Medical College, 2019)
Objective: Perinatal mortality rate is a sensitive indicator of quality and quantity of maternal and neonatal health services. Our aim was to study the causes of perinatal deaths and the trends of early neonatal deaths in NICU with respect to the causes and to estimate determinants of perinatal mortality and suggest remedial measures for its reduction. Background: Perinatal mortality is mirror reflection of maternal and child health and socioeconomic environment of community. It is influenced by various avoidable and unavoidable causes. It can be reduced by improving maternal and child health services and by health education. Methods: Our study was carried out in labour room and N.I.C.U. of Al Ameen Medical College, Vijayapura. We included still born babies with gestational age>28 weeks and early neonatal deaths i.e, till 7th day of life in this study. Fetomaternal factors like maternal age, religion, residence, parity, mode of delivery, booking status, antenatal complications, birth weight, congenital anomalies, neonatal complications influencing perinatal mortality rate were tabulated and analyzed. Cause of perinatal death was assessed. Results: Perinatal mortality rate was 33.84/1000 total births. Maternal factors like age more than 35 years, inadequate antenatal care, primiparity, grand multiparity, induced deliveries and neonatal factors like low birth weight, prematurity were associated with increased perinatal mortality. The leading cause of stillbirth was hypertensive disorders of pregnancy and prematurity for neonatal mortality. Conclusion: Apart from clinical causes high perinatal mortality was due to poverty, illiteracy, lack of health awareness, inadequate antenatal care and delayed referral. Health education, identification of high risk mothers, timely referral, advanced life support of preterm neonates should significantly help to reduce perinatal deaths.